2018
DOI: 10.1002/asi.24022
|View full text |Cite
|
Sign up to set email alerts
|

Congressional twitter use revisited on the platform's 10‐year anniversary

Abstract: The microblogging platform, Twitter, has been an extremely valuable tool for politicians in sharing information, fostering broader communication to constituents, and promoting their political stances. This article follows up on previous research from 2009 on this subject. We reexamined tweets from the US Congress collected in early 2017. We found Congressional tweeting habits and content have changed very little in the last 8 years. Overall, they tended to use Twitter to pass along political information and li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 3 publications
3
9
0
Order By: Relevance
“…Political parties are a mechanism to serve and facilitate electoral goals (Mayhew, 1974) and to maintain majority status (Aldrich, 1995). Prior work on Congressional tweets established that Republican and Democratic parties use Twitter for different communication activities (Golbeck et al, 2018; Hemphill et al, 2013; Russell, 2018), and we expect to see similar differentiation here. Another study of Twitter use in the U.K. Parliament found that the Labour Party members generated fragmented communication networks rather than a cohesive party (Adi, Erickson, & Lilleker, 2014).…”
Section: Introductionsupporting
confidence: 50%
See 3 more Smart Citations
“…Political parties are a mechanism to serve and facilitate electoral goals (Mayhew, 1974) and to maintain majority status (Aldrich, 1995). Prior work on Congressional tweets established that Republican and Democratic parties use Twitter for different communication activities (Golbeck et al, 2018; Hemphill et al, 2013; Russell, 2018), and we expect to see similar differentiation here. Another study of Twitter use in the U.K. Parliament found that the Labour Party members generated fragmented communication networks rather than a cohesive party (Adi, Erickson, & Lilleker, 2014).…”
Section: Introductionsupporting
confidence: 50%
“…This low-cost effort has the outsized potential to increase the interactions between elite and mass publics by publicly broadcasting their agenda and creating an accessible record of government action (Bruns and Highfield 2012). Twitter is a broadcasting device for politicians (Gainous and Wagner 2014;Golbeck et al 2018;Hemphill, Otterbacher, and Shapiro 2013), so being able to take advantage of its outreach capabilities is especially important to politicians and their staffers (Chi and Yang 2011). This public communication domain offers policymakers a relatively unfiltered credit claiming opportunity (Mayhew 1974) to highlight accomplishments and advertise a political brand.…”
Section: Tweeting Political Agendasmentioning
confidence: 99%
See 2 more Smart Citations
“…Legislators across the globe are increasingly using social media to communicate with their constituents, other legislators, and the news media. For example, as of 2018, every member of Congress has an active Twitter account (Golbeck et al 2018). The majority of elected o cials at the national level in Europe and in the EU parliament similarly have Twitter accounts (Scherpereel, Wohlgemuth and Lievens 2018;Kat Devlin and Cha 2019), and the platform is also widely used by legislators in Latin America (Munger et al 2018), and Asia (Yoon and Park 2014).…”
Section: Introductionmentioning
confidence: 99%